High Level Ethanol from Sugar Cane Molasses by a New Thermotolerant Saccharomyces cerevisiae Strain in Industrial Scale. (1st December 2013) - Fadel, M.; Keera, Abeer A.; Mouafi, Foukia E.; Kahil, Tarek
Abstract : A new local strain of S. cerevisiae F-514, for ethanol production during hot summer season, using Egyptian sugar cane molasses was applied in Egyptian distillery factory. The inouluum was propagated through 300 L, 3 m 3, and 12 m 3 fermenters charged with diluted sugar cane molasses containing 4%-5% sugars. The yeast was applied in fermentation vessels 65 m 3 working volume to study the varying concentrations of urea, DAP, orthophosphoric acid (OPA), and its combinations as well as magnesium sulfate and inoculum size. The fermenter was allowed to stay for a period of 20 hours to give time for maximum conversion of sugars into ethanol. S. cerevisiae F-514 at molasses sugar level of 18% (w/v), inoculum size of 20% (v/v) cell concentration of 3.0 × 10 8 /mL, and combinations of urea, diammonium phosphate (DAP), orthophosphoric acid (OPA), and magnesium sulfate at amounts of 20, 10, 5, and 10 kg/65 m 3 working volume fermenters, respectively, supported maximum ethanol production (9.8%, v/v), fermentation efficiency (FE) 88.1%, and remaining sugars (RS) 1.22%. The fermentation resulted 13.4 g dry yeast/L contained 34.6% crude protein and 8.2% ash. By selecting higher ethanol yielding yeast strain and optimizing, the fermentation parameters both yield and economics of the fermentation process can be improved.